Sensitivitas Real-Time Polymerase Chain Reaction dengan Primer Tanabe dalam Mendeteksi Gelatin Babi pada Confectionery - Said Naufal Hibaturrahman; Feri Kusnandar; Nancy Dewi Yuliana; Heryani Heryani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2023)
Gelatin is commonly used as a gelling and thickening agent in confectionery products and is considered a critical material in terms of its halal status. Real-time Polymerase Chain Reaction (real-time PCR) is frequently employed as an analytical tool to detect traces of pork in food items. Although the real-time PCR method using the Tanabe primer and Internal Positive Control (IPC) has been validated effectively, its sensitivity or Limit of Detection (LOD) for confectionery products has yet to be determined. This study aims to determine the sensitivity of real-time PCR with Tanabe primers and IPC towards the confectionery products (gummy candy, marshmallow, and lozenges). Confirmation of this method on commercial marshmallow products known to contain porcine gelatin was also carried out. In this study, the LOD (% w/w) of porcine gelatin in bovine gelatin was initially determined. The findings revealed that the LOD (% w/w) was 0.01% with a cycle threshold (Ct) value of 39.20±1.72. The next step involved determining the LOD (% w/w) of porcine gelatin in various confectionery products such as lozenges, gummy candy, and marshmallows. The LOD (% w/w) for lozenges and gummy candy was found to be 0.1% with Ct values of 40.93±0.15 and 38.72±0.18, respectively. Marshmallows exhibited an LOD of 0.01% with a Ct value of 41.14±2.96. Finally, this method was applied to commercial confectionery products containing porcine gelatin, and the real-time PCR effectively detected porcine gelatin with high sensitivity.